In vivo efficacy of pyrantel pamoate as a post-exposure prophylactic for rat lungworm (Angiostrongylus cantonensis). (August 2022) - Jacob, John; Steel, Argon; Kaluna, Lisa; Hess, Steven; Leinbach, Israel; Antaky, Carmen; Sugihara, Robert; Hamilton, Lindsey; Follett, Peter; Howe, Kathleen; Jacquier, Steven; Wongwiwatthananukit, Supakit; et al.
Abstract: Rat lungworm ( Angiostrongylus cantonensis ) is a neurotropic nematode, and the leading cause of eosinophilic meningitis worldwide. The parasite is usually contracted through ingestion of infected gastropods, often hidden in raw or partially cooked produce. Pharmaceutical grade pyrantel pamoate was evaluated as a post-exposure prophylactic against A. cantonensis . Pyrantel pamoate is readily available over-the-counter in most pharmacies in the USA and possesses anthelmintic activity exclusive to the gastrointestinal tract (GIT). Administering pyrantel pamoate immediately after exposure should theoretically paralyze the larvae in the GIT, causing the larvae to be expelled via peristalsis without entering the systemic circulation. In this study, pyrantel pamoate (11 mg/kg) was orally administered to experimentally infected rats at 0, 2-, 4-, 6-, or 8-h post-infection. The rats were euthanized six weeks post-infection, and worm burden was evaluated from the heart-lung complex. This is the first in vivo study to evaluate its efficacy against A. cantonensis . This study demonstrates that pyrantel pamoate can significantly reduce worm burden by 53–72% ( P  = 0.004), and thus likely reduce the severity of infection that is known to be associated with worm burden. This paralyzing effect of pyrantel pamoate on the parasite may also be beneficial for delaying the establishment of infection until a more suitable anthelmintic such as albendazole is made available to the patient. Graphical abstract: Image 1 Highlights: Pyrantel pamoate (PP) shows significant in vivo efficacy against A. cantonensis. Efficacy of PP was evaluated for the first time in an experimental animal model. Administering PP between 4 and 8 h post-exposure significantly reduces worm burden. PP is a new post-exposure prophylactic for rat lungworm disease.